In Vitro Propagation of Anthurium adreanum cv. Nitta through Organogenesis - Rizka Tamania Saptari; Masna Maya Sinta; Asmini Budiani (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Anthurium adreanum Lindl. cv. Nitta is an ornamental plant for cut flower industries. In vitro propagation enables a large scale production of high quality seedlings of A. adreanum quickly. The aim of this experiment was to overcome some problems in the in vitro propagation of A. adreanum, such as contamination, lack of plantlets vigor and low rate of survival in the acclimatization. In vitro propagation of A. adreanum was conducted via organogenesis from leaf explant. Explant sterilization using desogerm, antioxidant, alcohol, rifampicin, and NaOCl was the best because they reduced browning and contamination until 0 %. Organogenesis of A. adreanum was successfully initiated using MS medium added with 2,4-D and BAP at 1 mg L-1, which produced 74 shoots per explant. Shoots were best maturated in MS medium with a half strength of macro minerals added with 1 mg L-1 paclobutrazol. Survival rate increased by 7 and 14 days hardening treatment using double layer medium in the light culture room. Survival rate reached 89.3 % at 8 weeks after acclimatization.